PENGARUH KOMPENSASI, MOTIVASI KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT MORODADI BERKAH JAYA BOYOLALI - Ray Dewangga Pramanaya; Suprayitno Suprayitno; Sutarno Sutarno (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
This research was used to analyze the effect of compensation, work motivation and work discipline on the employee performance of PT Morodadi Berkah Jaya Boyolali. The total population in this study was 105 employees. The research sample of 83 employees with the sampling technique is proportional cluster random sampling. The technique of collecting data is done by using a questionnaire method. The results of this study indicate that partially or simultaneously compensation, work motivation and work discipline have a significant effect on employee performance.